Can Advanced Maternal Age Negatively Impact the Prognosis of Birth? An Observational Study at the Issaka Gazoby Maternity Center in Niamey, Niger - Kamaye Moumouni; Alido Soumana; Haoua Yahaya; Moumouni Garba; Oumarou Zaratou; Jina Lailatou; Amadou Aicha (European Scientific Journal, ESJ, 2018)
Background: Childbirth at an advanced age is increasing rapidly in the world. This is due to sociological changes and to the development of medically assisted procreation. There are still gaps in knowledge about the risks associated with pregnancy among older women. The objective of our study is to investigate the perinatal risk factors of pregnancy of women over the age of 35, who gave birth at Issaka Gazoby Maternity center in Niamey. Methods: It was a prospective case-control study that spread over 4 months (from January 1 to April 30, 2014). For each parturient whose age is greater than 35 years, we assigned them to two witnesses whose age is between 20 and 34 years. Data obtained from 100 women aged over 35 years and 200 women aged 20-34 years and their newborns were analyzed. Through univariate and multivariate analyses, we sought an association between maternal characteristics and perinatal prognosis. Results: The mean age of the case patients was 38.79 years. The mean age of the controls was 26.93 years. The mean parity of the cases was 6.83 children and that of the controls was 2.33 children. In the case patients, 50% of pregnancies were completed without complications compared to 51.5% of controls. The main complications were anemia, threat of preterm delivery, and pre-eclampsia. Seventy-three percent of older women underwent caesarean section. Obstructed labor, retro-placental hematoma, stationary dilation cervix, and pre-eclampsia were the main reasons for the caesarean section. The proportion of low birth weight was 27% among the case patients and 28% among the controls. Nine percent of the newborns in the cases had macrosomia as opposed to 4% in the control group. There was no significant relationship between maternal age and prematurity (OR = 0.24, 95% CI: 0.02 and 1.96, P = 0.13). Statistical analysis found no significant relationship between maternal age and low birth weight (OR = 2.37, 95% CI: 0.88 and 6.35, P = 0.07). The risk of having a low Apgar score was higher in the case patients (OR = 0.53, 95% CI: 0.32 and 0.88, P = 0.02). Older women were 2.87 times more likely to have a stillbirth child than controls (OR = 2.87, 95% CI: 1.41 and 5.83, P = 0.002). Conclusion: Neonatal mortality is higher in women over 35 years of age.